Data Mart of Climate Changes: a Proposed Approach to Support Sustainable Decision-Making - Alaa Khalaf Hamoud; Abdul-Haleem Ali Al Muhyi; Sadiq Salim Abdullah; Jasim Mohammed Dahr (Universitas Komputer Indonesia, 2026)
The growing focus on climate change requires effective data-driven decision-making to promote sustainability. This study proposes a data mart framework to manage and analyze climate datasets from a station in Basrah, Iraq. The model aims to support sustainable decisions by examining factors like temperature, solar radiation, rainfall, wind direction, humidity, and wind speeds at various altitudes. A star schema facilitates online analytical processing (OLAP) and future advanced analytics. Power BI is utilized for data visualization, providing actionable insights to stakeholders via real-time indicators and customizable dashboards. This framework aids short-term decision-making regarding climate impacts, with future work incorporating machine learning for predictive pattern forecasting.